Reformulation and strengthening of return-of-service (ROS) schemes could change the narrative on global health workforce distribution and shortages in sub-Saharan Africa. Issue 4 (21st September 2020) - Mabunda, Sikhumbuzo A; Angell, Blake; Yakubu, Kenneth; Durbach, Andrea; Joshi, Rohina
Abstract : Despite policies for addressing shortages and maldistribution of health professionals, sub-Saharan Africa continues to experience shortages and maldistribution of skilled health professionals. Policies such as return-of-service schemes or state-funded educational initiatives do not seem to be achieving their intended objectives, potentially due to poor design, implementation; and lack of monitoring and evaluation of the strategies. A focus by global health experts on strengthening and reformulating educational initiatives offers potential for producing, retaining and recruiting health professionals.